2019
DOI: 10.1177/2055116919853898
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyglutaric aciduria as a cause for seizure-like episodes in a domestic shorthair cat

Abstract: Case summary A 14-month-old male castrated domestic shorthair cat, which 2 months prior to presentation underwent hindlimb amputation following a road traffic accident, presented for investigation of four suspected generalised tonic–clonic seizures. Neurological examination was unremarkable. Routine blood work (haematology, biochemistry, ammonia, preprandial bile acids) was unremarkable. MRI of the brain identified marked symmetrical T2-weighted hyperintensities of the cerebellum and brainstem, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…Epileptic seizure activity has also been reported in a cat previously with 2-HGA; however, the phenotype of the epileptic seizure activity was different. In the previous case [ 5 ], generalized tonic-clonic epileptic seizures were reported, while our case displayed multiple episodes of running frantically around the house, often in circles, for approximately 30–60 s, bumping into obstacles, having altered mentation and autonomic signs, including salivation and often urination. These episodes are similar to those described in some dogs with L-2-HGA [ 6 ].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Epileptic seizure activity has also been reported in a cat previously with 2-HGA; however, the phenotype of the epileptic seizure activity was different. In the previous case [ 5 ], generalized tonic-clonic epileptic seizures were reported, while our case displayed multiple episodes of running frantically around the house, often in circles, for approximately 30–60 s, bumping into obstacles, having altered mentation and autonomic signs, including salivation and often urination. These episodes are similar to those described in some dogs with L-2-HGA [ 6 ].…”
Section: Discussionmentioning
confidence: 56%
“…In this study, we identified a homozygous L2HGDH :c.1301A>G missense variant in a domestic cat with a history of suspected seizure-like episodes, corresponding MRI-changes and markedly elevated levels of L-2-hydroxyglutaric acid in the obtained urine sample. The combination of the MRI abnormalities (i.e., multifocal, bilaterally symmetrical, T2W hyperintensities, primarily affecting the grey matter in the mesencephalon and metencephalon) appears to be a common feature for L-2-HGA in cats [ 5 ]. Epileptic seizure activity has also been reported in a cat previously with 2-HGA; however, the phenotype of the epileptic seizure activity was different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is caused by genetic variants affecting the L2HGDH gene encoding L‐2‐hydroxyglutarate dehydrogenase and has an autosomal recessive mode of inheritance. 1 , 2 , 3 , 4 , 5 , 6 , 7 Disease‐causing variants have been reported in humans, dogs (Staffordshire bull terrier, Yorkshire terrier) and 1 cat. 1 , 2 , 3 , 4 , 5 The clinical signs and magnetic resonance imaging (MRI) findings in dogs and cats with L2HGA have been reported previously.…”
Section: Introductionmentioning
confidence: 99%